EVALUACIÓN DE LA EDAD COMO FACTOR DE RIESGO DE SEROPOSITIVIDAD A Sarcocystis sp. EN ALPACAS - Castro C., Eduardo (2004)
The objective of the present study was to evaluate the age of alpacas as a risk factor to become infected with Sarcocystis sp. Blood samples were collected from 941 alpacas reared at the SAIS Túpac Amaru (Junín, Peru). Samples were stratified for statistical analysis in 5 age groups (<1, 1, 2, 3, ? 4 years). The sera were analyzed by the indirect ELISA test for the detection of Sarcocystis antibodies. The results showed 844 positive samples representing a seroprevalence of 89.7 ± 1.9% (46, 98, 96, 95 and 95% for < 1, 1, 2, 3, and ? 4 years old, respectively). There were statistical differences between age and the presence of Sarcocystis sp. antibodies (p<0.05).